Pesticide Management in the Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
workshop held at the offices of the Institute of Research, Extension and Training in Agriculture (IRETA) at Alafua Campus, Samoa, from 7-11 September 1998